Analisis Gaya Bahasa Dalam Film 1 Kakak 7 Ponakan Karya Yandy Laurens : Analysis of language style in the film 1 Kakak 7 Ponakan by Yandy Laurens - Mimza Nazilatul 'Ulya; Oktarina Puspita Wardani (Jubah Raja : Jurnal Bahasa, Sastra, Dan Pengajaran, 2026)
The research focuses on analyzing the types of language styles found in the film 1 Kakak 7 Ponakan by Randy Laurens. This study aims to : 1) describe and identify the types of language styles found in the caracter dialogues of the film 1 Kakak 7 Ponakan , 2) describe the functions of the language styles. This research uses a descriptive qualitative approach with a stylistic study. The data source consists of character dialogues from the film 1 Kakak 7 Ponakan by Yandy Laurens with a duration of 131 minutes. Data collection was carried out using the observation method and note-taking technique. The result show that 58 dialogue styles. Comparative language styles were found from four groups, broken down into 18 language styles. Comparative language styles were found ( 17 data) including simile, metaphor, personification, allegory, ellips, and allusion. Contrasting language styles were found ( 26 data) including irony , litotes, antithesis, climax, cynicism, sarcasm, anticlimax, and hyperbole. Cohesive language styles were found ( 8 data) including euphemism, rhetorical, and dysphemism. Repetitive language styles were found ( 7 data) including alliteration and epizeuxis. The functions of language style in this film are to build character characterization, build dramactic conflict, convevy moral messages.